Unusual catalytic strategy by non-heme Fe(ii)/2-oxoglutarate-dependent aspartyl hydroxylase AspH - Krishnan, A; Waheed, SO; Varghese, A; Cherilakkudy, FH; Schofield, C; Karabencheva-Christova, TG (Royal Society of Chemistry, 2024)
Biocatalytic C-H oxidation reactions are of important synthetic utility, provide a sustainable route for selective synthesis of important organic molecules, and are an integral part of fundamental cell processes. The multidomain non-heme Fe(ii)/2-oxoglutarate (2OG) dependent oxygenase AspH catalyzes stereoselective (3R)-hydroxylation of aspartyl- and asparaginyl-residues. Unusually, compared to other 2OG hydroxylases, crystallography has shown that AspH lacks the carboxylate residue of the characteristic two-His-one-Asp/Glu Fe-binding triad. Instead, AspH has a water molecule that coordinates Fe(ii) in the coordination position usually occupied by the Asp/Glu carboxylate. Molecular dynamics (MD) and quantum mechanics/molecular mechanics (QM/MM) studies reveal that the iron coordinating water is stabilized by hydrogen bonding with a second coordination sphere (SCS) carboxylate residue Asp721, an arrangement that helps maintain the six coordinated Fe(ii) distorted octahedral coordination geometry and enable catalysis. AspH catalysis follows a dioxygen activation-hydrogen atom transfer (HAT)-rebound hydroxylation mechanism, unusually exhibiting higher activation energy for rebound hydroxylation than for HAT, indicating that the rebound step may be rate-limiting. The HAT step, along with substrate positioning modulated by the non-covalent interactions with SCS residues (Arg688, Arg686, Lys666, Asp721, and Gln664), are essential in determining stereoselectivity, which likely proceeds with retention of configuration. The tetratricopeptide repeat (TPR) domain of AspH influences substrate binding and manifests dynamic motions during catalysis, an observation of interest with respect to other 2OG oxygenases with TPR domains. The results provide unique insights into how non-heme Fe(ii) oxygenases can effectively catalyze stereoselective hydroxylation using only two enzyme-derived Fe-ligating residues, potentially guiding enzyme engineering for stereoselective biocatalysis, thus advancing the development of non-heme Fe(ii) based biomimetic C-H oxidation catalysts, and supporting the proposal that the 2OG oxygenase superfamily may be larger than once perceived.